2018
DOI: 10.15761/ccsr.1000103
|View full text |Cite
|
Sign up to set email alerts
|

Recovery after childbirth: A qualitative study of postpartum women

Abstract: Implication statementResearch in the postpartum period has been largely quantitative and focused on obstetric dysfunction, major depression and impact of epidural analgesia. The purpose of this study was to describe women's perception of postpartum pain and identify specific impediments to better pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…[ 12 ] Although Baghirzada et al . (2018) in their qualitative study titled “Postpartum Recovery”, considered social recovery from a societal perspective with exploratory theme of utilization of care resources in the society,[ 13 ] Shoorab et al . (2019) in a qualitative study regarding women's experiences of emotional recovery from childbirth-related perineal trauma reported that fecal incontinence following sever perineal trauma threatened the social recovery of affected women due to disruption of women's social relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 12 ] Although Baghirzada et al . (2018) in their qualitative study titled “Postpartum Recovery”, considered social recovery from a societal perspective with exploratory theme of utilization of care resources in the society,[ 13 ] Shoorab et al . (2019) in a qualitative study regarding women's experiences of emotional recovery from childbirth-related perineal trauma reported that fecal incontinence following sever perineal trauma threatened the social recovery of affected women due to disruption of women's social relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Findings of different studies showed that physical and psychological aspects are mostly emphasized in postpartum recovery period, while less attention has been paid to other dimensions including social aspects of women's recovery. [ 9 13 16 ]…”
Section: Introductionmentioning
confidence: 99%